T24. CHANGES IN TELOMERE LENGTH IN YOUNG PEOPLE WITH FIRST EPISODE PSYCHOSIS: A 12-MONTHS FOLLOW-UP STUDY. (18th May 2020) - Ayora, Mirian; Fraguas, David; Recio, Sandra; Diaz-Caneja, Covadonga M; Blasco, Maria A; Arango, Celso
Abstract: Background: Cellular aging is associated with the appearance of several chronic organic diseases, and many neuropsychiatric disorders such as schizophrenia spectrum disorders, which include psychotic disorders. Telomeres are one of the biomarkers of this cellular aging. Researches have shown that shorter telomere length is a biomarker of oxidation and cellular aging. Recent studies have concluded that patients with a first psychotic episode (FEP) have shorter telomere length than healthy controls (HC). However, there is no published data on the change in telomere length in the first years of illness. The purpose of this study is to evaluate the changes in telomere length measured in peripheral blood mononuclear cells (PBMCs) in a sample of patients with early-onset psychosis and healthy subjects. Methods: This study included 10 young patients with FEP (50% female, mean age 18.4 years) and 10 young HC (60% female, mean age 16.4 years). PBMCs telomere length was determined using high-throughput quantitative fluorescence in situ hybridization (HT Q-FISH) at baseline and 12-month follow-up. We analysed in our sample of patients if there are significant differences according to the diagnosis and antipsychotic treatment. Results: At baseline, we did not find significant differences in telomere length between FEP patients and HC. After one-year follow-up, it was found that telomere length is shorter in patients with FEP than in HC (p=0.007). The diagnostics in the patients' group were: 60% schizophrenia and 40% other diagnoses (20% psychosis not specified and 20% bipolar disorder). There was no significant difference between changes in telomeres length and diagnosis (p = 0.840). The antipsychotic treatment in the patients' group after 12 months was: 20% risperidone, 50% aripiprazole, 10% clozapine, 10% paliperidone and 10% quetiapine. We didn′t find a strong association between the shortening of telomeres and the cumulative dose of antipsychotics. Discussion: This is one of the first studies where it has been analysed a longitudinal data of telomere length. It is shown that patients with the first episode of psychosis have significantly shorter telomere length than healthy controls. Changes in telomere length during the first years of illness can represent an early marker of accelerated cellular aging. Further studies are needed with a larger sample to know mechanisms responsible for accelerating aging and the role of oxidative stress in the pathogenesis of psychosis.